2020
DOI: 10.1038/s41388-020-01410-z
|View full text |Cite
|
Sign up to set email alerts
|

IMPAD1 and KDELR2 drive invasion and metastasis by enhancing Golgi-mediated secretion

Abstract: Summary Non-small cell lung cancer (NSCLC) is the deadliest form of cancer worldwide, due in part to its proclivity to metastasize. Identifying novel drivers of invasion and metastasis holds therapeutic potential for the disease. We conducted a gain-of-function invasion screen, which identified two separate hits, IMPAD1 and KDELR2, as robust, independent drivers of lung cancer invasion and metastasis. Given that IMPAD1 and KDELR2 are known to be localized to the ER-Golgi pathway, we studied their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Based on our prior screen results [ 6 , 7 ] and the in silico findings, we hypothesized that MBIP amplification may participate in controlling cellular migration and invasion to drive metastasis. To test this hypothesis, we generated murine 393P, 344SQ, 531LN3 and human H157 lung cancer cell lines with doxycycline inducible MBIP expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our prior screen results [ 6 , 7 ] and the in silico findings, we hypothesized that MBIP amplification may participate in controlling cellular migration and invasion to drive metastasis. To test this hypothesis, we generated murine 393P, 344SQ, 531LN3 and human H157 lung cancer cell lines with doxycycline inducible MBIP expression.…”
Section: Resultsmentioning
confidence: 99%
“…There is an urgent unfulfilled need to find novel therapeutically targetable drivers for lung cancer metastasis since the clinical options for treatment of metastatic NSCLC are still largely limited. As a follow-up study to our recent in vitro and in vivo gain-of-function screens that identified potential genes promoting invasion and metastasis, here we investigated the mechanistic and clinical relevance of MBIP in the context of NSCLC metastasis [ 6 , 7 ]. MBIP has been reported to be clinically associated with papillary thyroid cancer T staging and its genomic amplification has been found in significant proportions of lung adenocarcinomas in combination with other drivers like NKX2–1 [ 15 , 16 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During progression, tumor cells frequently display increased secretory activity, which associates with structural adaptations of the secretory apparatus, such as expansion of the Golgi network and optimization of vesicular trafficking ( 53 56 ), correlating with poor prognosis ( 57 60 ). However, the mechanisms responsible for reprogramming the secretory machinery in cancer cells have remained elusive.…”
Section: Mut-p53 Enhances Vesicular Trafficking and Secretionmentioning
confidence: 99%
“…The functions of KDELRs are associated with cancer biology (19,(27)(28)(29)(30), especially in glioma: KDELR1 can significantly reduce the expression of the ER transcription factor CREB3 (27) and block hypoxia-induced autophagy in glioblastoma (28); KDELR2 has been associated with the median survival rate of non-small cell lung cancer (29), and it promotes glioblastoma tumorigenesis, which is regulated by hypoxia-inducible factor 1 (HIF-1) (30). Knockdown of KDELR2 has been shown to reduce cell viability, promote cell cycle arrest, and induce apoptotic cell death by targeting cell cycle proteins (31) In addition, KDELR3 promotes high melanoma metastasis (19).…”
Section: Introductionmentioning
confidence: 99%